Between 1990s' Nostalgia and 'LGBT-friendly' Tokyo Olympics: Representations of LGBTQ People in NHK's Morning Drama Series. Issue 2 (4th May 2021) - Thelen, Timo
ABSTRACT: This article investigates the first representation of LGBTQ characters in an asadora (Japanese morning drama), arguably the most conservative and 'traditional' series format in contemporary Japanese television. I suggest that the introduction of an openly gay character in 2018's Hanbun, aoi can be accounted for by appeal to two factors. First, this particular series' thematic focus on failure, manga, and nostalgia for the 1990s, including the 'gay boom' associated with that decade, motivated the depiction of a gay character. Second, Japan's political agenda in the 2010s encouraged the positive reinterpretation of sexual minorities as important new consumers and a tourist niche, especially with an eye to the blockbuster international event that was meant to be the 2020 Tokyo Olympics. However, the superficial and highly stereotyped representation offered in Hanbun, aoi reflects a contemporary strategy in Japanese mass media and politics: namely, that of celebrating 'LGBT-friendliness' as a promotional or marketing move, while avoiding substantive discussions about critical LGBTQ issues like discrimination and legal rights.